POTRET HARMONI ANTAR SISWA-SISWI BERAGAMA DI SMA TIGA MARET YOGYAKARTA - Furqon, Muhammad (Jurnal Sosiologi Agama, 2020)
This research analyzed harmony between students in religious difference in SMA Tiga Maret Yogyakarta using qualitative methode. This study indicate (1) Adaptation (adaptation) The adaptation function for students has occurred since the past and has been harmonious. (2) Achievement of the goal (goal attainment) With harmonious students, the three March High Schools in Yogyakarta interact with each other (3) Integration (integration) In Three March High School Yogyakarta is the role of schools and religious teachers in regulating relations between students of different religions in order to maintain harmony in a system both within the maupuan school environment in the wider community. (4) Latency (maintenance of patterns) In interactions between students of different religions in SMA Tiga Maret Yogyakarta Latency (maintenance of patterns) is divided into 3 parts, namely opening oneself to the preservation efforts undertaken so that harmony between students of different religions is continued with attitudes be vigilant and finally improve, where when a conflict occurs in the name of a religious community causing disunity is an effort that is no less important.